Using Glycerol as a Sole Carbon Source for Clostridium beijerinckii Fermentation - Vorapat Sanguanchaipaiwong (2018)
© 2017 The Authors. Published by Elsevier Ltd. Butanol is a promising biofuel with its fuel properties which are similar to gasoline and able to be synthesized from acetone-butanol-ethanol fermentation of Clostridium sp. This study has been focused on using glycerol, a by-product from biodiesel manufacturing as a carbon source for Clostridium beijerinckii TISTR 1390. The culture was cultivated at 37°C in P2 medium with 20-60 g/L glycerol under anaerobic condition, compared with glucose as a control. Samples were collected periodically for the analysis of viable cell concentration, reducing sugar and metabolite concentrations. It has been found that C. beijerinckii grown much slower in glycerol. After 168 h cultivation, the cell growth in 20 g/L glycerol has achieved the maximum concentration of 4.78 × 106CFU/mL. In P2 medium containing glucose, the amount of viable cell (3.93 x 106CFU/mL with 20 g/L glucose) had reached the maximum level at 24 h. The much longer period for highest cell number might be the reason that C. beijerinckii could not produce butanol from merely glycerol. On the other hand, the butanol concentration of 8.12 g/L was obtained from 60 g/L glucose. Glycerol probably induced C. beijerinckii in switching to a reductive pathway.